RESIDENTIAL PREFERENCES TOWARDS URBAN AND SUBURBAN AREAS AND THEIR RELATIONSHIP WITH DEMOGRAPHIC CHARACTERISTICS - Petrić, Jasna J (Arhitektura i urbanizam, 2014)
Urban sprawl is, among all, also the result of voluntary or induced resettlement of population from the inner city to urban periphery, or by in-migration to peripheral parts of cities where the origin of migrants is in other settlements. The focus of this paper is on the influence that residential preferences have on suburbanization, with the emphasis on analysis of the residential choice and certain population groups’ tendencies to prioritise living in suburbs or the inner-city living. Theoretical considerations which are set in this paper initiate with residential preference components and the hypothesis of change in dominant motives for residential choice throughout family and individual’s lifecycle. Then, the demographic data have been analysed according to the latest Census results in the two pilot-areas of urban and suburban type in Belgrade. Additional research on residential preferences are founded on preparation of specific questionnaire which would enable application of more powerful statistical techniques, especially a wider use of measuring scales for the variables deriving from the questionnaire, and formulation of a model for prediction of different population groups’ residential preferences in urban and suburban settings.